Shifting the Center: Relocating Refugee Men in Strategies Aiming to Address Violence Against Women - Maturi, Jenny (Violence against women, 2023)
This article aims to problematize individualistic strategies developed in western institutions to address violence against women and suggests more collective responses that engage refugee men. The data comes from a qualitative research project in Southeast Queensland, Australia. Thirty-one interviews with frontline workers from domestic violence and refugee settlement organizations reveal dissenting voices that challenge the hegemony of dominant groups who either advocate gender equality or overemphasize cultural differences. These dissenting voices suggest new knowledge being mobilized by refugees and associated communities, presenting opportunities for nongovernmental organizations and community groups to find ways to align across their differences toward a common goal.